Clinical analysis of infectious mononucleosis complicated with acute acalculous cholecystitis - Gao, Caijie; Cao, Liming; Mei, Xiaoli (Frontiers in Pediatrics, 2024)
This study aimed to investigate specific clinical diagnostic methods for children with infectious mononucleosis (IM) complicated by acute acalculous cholecystitis (AAC).We conducted a retrospective analysis of 171 cases of IM diagnosed in the infectious disease ward of Children's Hospital of Nanjing Medical University between January 2020 and December 2020. All IM patients underwent abdominal ultrasound examinations to assess the liver, gallbladder, and spleen. Fourteen patients with symptoms of AAC underwent a follow-up assessment one week later.The estimated incidence of AAC in hospitalized IM children was 8.2%.Both groups of patients presented with fever, abdominal pain, and eyelid edema upon admission. Characteristic radiological findings of AAC were observed, including gallbladder (GB) distention, increased GB wall thickness and increased common bile duct diameter. Analysis of laboratory results revealed no statistically significant differences in leukocyte, absolute lymphocyte count, CD3+, CD3+CD4+, CD3+ CD8+, Aspartate Aminotransferase (AST), Alanine Aminotransferase (ALT), or Gamma-Glutamyl Transferase (GGT) levels between the AAC(+) and AAC(-) groups on admission. However, these parameters were not significant risk factors for AAC. After discharge, relevant indicators in non-AAC patients gradually decreased to normal levels, while those in AAC(+) patients did not show a significant decrease.While cases of IM complicated by AAC are relatively uncommon, the utilization of abdominal ultrasound offers a reliable tool for confirming this diagnosis. Routine abdominal ultrasound examinations are recommended for IM patients to improve early detection and treatment of associated conditions.